Solution of Nonlinear Partial Differential Equations by New Laplace Variational Iteration Method. (25th March 2014) - Hilal, Eman M. A.; Elzaki, Tarig M.
Abstract : The aim of this study is to give a good strategy for solving some linear and nonlinear partial differential equations in engineering and physics fields, by combining Laplace transform and the modified variational iteration method. This method is based on the variational iteration method, Laplace transforms, and convolution integral, introducing an alternative Laplace correction functional and expressing the integral as a convolution. Some examples in physical engineering are provided to illustrate the simplicity and reliability of this method. The solutions of these examples are contingent only on the initial conditions.